Computer Modelling of Heliostat Fields by Ray-Tracing Techniques: Simulating the Mechanical Rotations - José Carlos Garcia Pereira; Luís Guerra Rosa (Applied Sciences)
In this work, solar concentrating heliostat fields are modeled using accurate solar-tracking algorithms and a wide range of rotation models to investigate the parameters controlling the mechanical efficiency of these solar facilities. Iterative procedures are first described to determine the rotation angles needed to properly orient a single heliostat for the most commonly used mechanical models, including the azimuth-elevation, tilt-roll, and target-aligned models. These mathematical techniques were integrated into our Light Analysis Modelling (LAM) software and used to study a realistic heliostat field with six different mechanical rotation models for the full year of 2024 and a daily working range of 08:00–16:00 Local Time (LCT). Two locations were chosen, representing the highest and lowest latitudes from the SFERA-III EU list of solar concentrating facilities with heliostat fields: Jülich (Germany) and Protaras (Cyprus). The results obtained show that tilt-roll models require less angular rotation (−15.2% in Jülich, −20.2% in Protaras) and a narrower angular range (−14.5% in Jülich, −20.2% in Protaras) than azimuth-elevation models. Seldom-used target-aligned models are more efficient with tilt-roll rotations (compared with the tilt-roll model: −35.1% rotations in Jülich, −29.2% in Protaras; −12.3% angular range in Jülich, −14.3% in Protaras) and less efficient with azimuth-elevation rotations (compared with the azimuth-elevation model: +53.2% rotations in Jülich, +39.2% in Protaras; +96.2% angular range in Jülich, +87.5% in Protaras).